2022
DOI: 10.1039/d1ta07678g
|View full text |Cite
|
Sign up to set email alerts
|

In situ construction of hetero-structured perovskite composites with exsolved Fe and Cu metallic nanoparticles as efficient CO2 reduction electrocatalysts for high performance solid oxide electrolysis cells

Abstract: Solid oxide electrolysis cells (SOECs) have been widely used for efficient conversion of CO2 into valuable fuels and chemicals utilizing clean and renewable alternative energy sources. However, the scarcity of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…[63] Such morphology could maintain a high active surface for the catalysis (a higher specific surface area of the reduced SF1.5MC was demonstrated in Figure S4, Supporting Information) and a reasonable durability under realistic operating conditions. [63] were also fabricated and tested in the same way for SF1.5MC (Figure S5, Supporting Information). The activation energy of the electrodes for H 2 oxidation were evaluated by the EIS tests of the symmetrical cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[63] Such morphology could maintain a high active surface for the catalysis (a higher specific surface area of the reduced SF1.5MC was demonstrated in Figure S4, Supporting Information) and a reasonable durability under realistic operating conditions. [63] were also fabricated and tested in the same way for SF1.5MC (Figure S5, Supporting Information). The activation energy of the electrodes for H 2 oxidation were evaluated by the EIS tests of the symmetrical cells.…”
Section: Resultsmentioning
confidence: 99%
“…The differences in the current densities at 1.1-1.4 V suggested that the hetero-interfaces in the reduced SF1.5MC composite electrode may function as a highly active catalyst for the CO 2 R. It should be noted that the current densities of the reduced SFMC electrode within the short-term potentiostatic measurements began to degrade at the high applied voltages over 1.2 V. The degradation may be caused by the structural defects of the reduced SFMC perovskite oxides, which were aggravated by the applied high potentials of 1.3 V and 1.4 V. [18] The reduced SF1.5MC-GDC fuel electrode with the hetero-interfaces has exhibited its potential of the efficient conversion for CO 2 , indicated by its highest current density at 1.3 V among the other SOECs reported recently (Figure 5c, Table S5, Supporting Information). [3,5,14,17,18,35,37,63,[81][82][83][84] Figure 5. CO 2 electrolysis performance and durability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Copper (Cu) has been determined to be an effective electrocatalyst to induce the dimerization of adsorbed *CO to C 2+ product. [2][3][4][5][6][7][8][9] Numerous studies have been reported on Cu-based electrocatalysts with impressive faradaic efficiency (FE) and current density for CO 2 RR. [10][11][12][13] Unfortunately, the critical roles of Cu sites particularly the argument on the positively charged Cu + species, remain unclear.…”
Section: Introductionmentioning
confidence: 99%